2003
DOI: 10.1021/jp021976w
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Internal Rotation of the Hydroxylic Group of the Enol Form of Guanine

Abstract: Emphasis was placed in the present work on a density functional theory and Hartree−Fock study of the internal rotation of the hydroxylic group of the enol form of guanine. This was achieved by monitoring the behavior of energy, chemical potential, hardness, electrophilicity, and polarizability along the torsional coordinate. An energy barrier of about 9.5 kcal/mol was found about midway between two stable planar conformations. The analysis of the behavior of reactivity descriptors shows that the principles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
4
16
0
2
Order By: Relevance
“…24,25 La Ecuación 5 presenta un problema de discontinuidad en áto-mos y moléculas cuando se combina con la aproximación de diferencias finitas, dando lugar a tres expresiones de FF. (6) En el punto r, f + (r) mide la reactividad para un ataque nucleofílico, f -(r) mide la reactividad para un ataque electrofílico y f°(r) describe un ataque por un radical y se obtiene como el promedio aritmético de f + (r) y f -(r). La cuantificación de la función es posible a través de un esquema de condensación sobre una región atómica, se pueden escribir las FF usando las técnicas de análisis poblacional; 26,27 esto da lugar a las siguientes ecuaciones de trabajo: (7) donde q k (N) denota la población electrónica del átomo k del sistema de referencia, más correctamente denominado q k (N 0 ).…”
Section: Propiedades Localesunclassified
See 1 more Smart Citation
“…24,25 La Ecuación 5 presenta un problema de discontinuidad en áto-mos y moléculas cuando se combina con la aproximación de diferencias finitas, dando lugar a tres expresiones de FF. (6) En el punto r, f + (r) mide la reactividad para un ataque nucleofílico, f -(r) mide la reactividad para un ataque electrofílico y f°(r) describe un ataque por un radical y se obtiene como el promedio aritmético de f + (r) y f -(r). La cuantificación de la función es posible a través de un esquema de condensación sobre una región atómica, se pueden escribir las FF usando las técnicas de análisis poblacional; 26,27 esto da lugar a las siguientes ecuaciones de trabajo: (7) donde q k (N) denota la población electrónica del átomo k del sistema de referencia, más correctamente denominado q k (N 0 ).…”
Section: Propiedades Localesunclassified
“…Esta herramienta ha sido usada para probar varios sistemas moleculares. [5][6][7][8] El estudio teórico en el modelo de la Teoría de Funcionales de la Densidad, puede ayudar como una guía en la reactividad de los halobencenos. La Teoría de Funcionales de la Densidad es un modelo conceptual para relacionar los cálculos con conceptos tales como potencial químico electrónico (μ), 9-12 dureza química (η) 9-13 y electrofilicidad (ω), 14 conceptos que nos ayudan a entender el comportamiento electrónico de los sistemas.…”
Section: Introductionunclassified
“…It is shown that ω is a useful descriptor for reactivity and is frequently used in analysis of chemical reactivity of different molecules. [28][29][30][31][32][33][34][35][36][37][38][39] Variations of this quantity during molecular vibrations, 40,41 internal rotations, 42,43 and chemical reactions 40,[44][45][46][47][48][49] have been recently studied. Chamorro et al 40 found that under constants μ and ( ) r ν , there would be a minimum electrophilicity principle along a reaction path.…”
Section: Introductionmentioning
confidence: 99%
“…Following the PMH principle, molecular systems at equilibrium tend toward states of higher hardness, and, as a consequence, transition states are expected to present a minimum hardness value [4]. This principle was confirmed for the isomerization reaction of guanine, and good linear correlations between the rotational energy of the hydroxyl group and the chemical potential, hardness, and electrophilicity index along the reaction path were established [5].…”
Section: Introductionmentioning
confidence: 94%